The Lower Palaeolithic colonisation of Europe : antiquity, magnitude, permanency and cognition - Ling, Victoria (BAR international series ;, 2011)
"The Lower Palaeolithic colonisation of Europe has traditionally been considered in terms of its antiquity. However, whilst establishing the antiquity of European colonisation is vital for gauging the range expansion of Pleistocene hominins, this alone provides little insight to the pattern of that colonisation. That is, establishing antiquity alone does not greatly help to address questions such as: how many dispersals were there into Europe? How long did each dispersal last? Were some regions more densely populated than others? This research investigates the pattern and character of the Lower Palaeolithic hominin colonisation of Europe, approached from four angles: 1. Long versus short chronology (antiquity of colonisation); 2) Dispersals versus in situ evolution (permanency of colonisation); 3) Population continuity versus discontinuity (palaeodemography of colonisation); 4) Mode 1 versus Mode 2 (cognitive capabilities of contemporaneous populations)." --Publisher's website.